2018
DOI: 10.47604/ijscm.767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Collaborative Planning on Performance of Pharmaceutical Firms in Kenya

Abstract: later

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…, 2020). From previous studies it was confirmed that there is a positive correlation between SC agility and performance (Betts and Tadisina, 2009; Alkrait and Almaktoom, 2021; Loury-Okoumba and Mafini, 2021); SC resilience and SC performance (Kariuki et al. , 2018; Chowdhury et al.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…, 2020). From previous studies it was confirmed that there is a positive correlation between SC agility and performance (Betts and Tadisina, 2009; Alkrait and Almaktoom, 2021; Loury-Okoumba and Mafini, 2021); SC resilience and SC performance (Kariuki et al. , 2018; Chowdhury et al.…”
Section: Discussionmentioning
confidence: 79%
“…From previous studies it was confirmed that there is a positive correlation between SC agility and performance (Betts and Tadisina, 2009;Alkrait and Almaktoom, 2021;Loury-Okoumba and Mafini, 2021); SC resilience and SC performance (Kariuki et al, 2018;Chowdhury et al, 2019); IT capabilities and SC performance (Wu et al, 2006;Niu, 2010;Mashreghi et al, 2018). Similarly, SC agility (Alkrait and Almaktoom, 2021), SC resilience (Kariuki et al, 2018) and IT capability (Niu, 2010;Mashreghi et al, 2018) have significant influence on SC performance. SC agility and SC resilience have a positive and significant relationship with SC performance (Carvalho et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Every organization engaged in product creation or service provision must procure diverse raw materials and components, efficiently oversee inventories and manufacturing processes, and ultimately provide a superior product to their end consumer within the specified timeframe (7).…”
Section: Supply Chain Management Analyticsmentioning
confidence: 99%